Could CSR Practices Increase Employee Affective Commitment via Moral Attentiveness? - Uçkun, Seher; Arslan, Aykut; Yener, Serdar (Sustainability, 2020)
The impact of corporate social responsibility (CSR) activities on companies’ macroeconomic indicators (financial performance, sustainability) has been the subject of many studies. However, more recently, the effect of CSR activities on individual variables (microeconomic indicators) has begun to attract attention. Although CSR itself is founded on the moral roots of the society in which it operates, it seems that the effect of individuals’ moral attentiveness has been neglected. The CSR effect, which is the focus of this study, is examined using three dimensions to understand how CSR can directly and indirectly affect the organizational commitment of employees. A theoretical model is developed in this paper, the focus of which is on the ethical framework of CSR and the proposition that it may have an effect on employees. The sample comprises individuals working in two of the country’s most important private production facilities in the western capital of Turkey. An online questionnaire form was prepared and shared. The online form was active between 2 March 2020 and 11 May 2020. Out of 472 forms, 465 were usable and, therefore, used in the analyses. We found proof for most of our assertions. Implications and future research suggestions are discussed.